E-Government Dan Manajemen Pelayanan Publik : (Studi Tentang upaya Pengembangan E-Government Pemerintah Daerah Kabupaten Bima) - Sri Asmiatiningsih (Universitas 17 Agustus 1945, 2022)
The purpose of this research is to find out the efforts to develop e-government and improve public services in Bima Regency. This study used descriptive qualitative method. The subjects of this study were selected through a nonprobability sampling technique, using a purposive sampling technique. The informants in this study were 20 web admins of the Regional War Work Unit/OPD of the Regional Government of Bima Regency. Data collection techniques consist of observation, interviews, and documentation. The results of the study show that support for the implementation of e-government in public services in Bima Regency has been provided, although it is not optimal, this is due to different budget allocations in each Regional War Work Unit/OPD. On the capability side, in general the literacy level of Bima Regency Government employees is still low, especially senior employees. Meanwhile, on the value side, e-government managers already understand the benefits and importance of information technology applications in public services. In order for the implementation of e-government to run optimally, it is necessary to make a clear legal umbrella and make a grand design for the development of e-government including preparing the budget. Regarding employees with low literacy, it is necessary to plan continuous Information Technology training and in the future the Bima district government must plan to recruit employees with an educational background in information technology.